Russia’s Political Activity in Achieving the Sustainable Development Goals - V. I. Andreeva; N. A. Vasilyeva (Евразийская интеграция: экономика, право, политика, 2025)
Peace, justice and strong institutions (Sustainable Development Goal 16) and partnership for the goals (Sustainable Development Goal 17) are gathering popularity among scientists, politicians and civil society in the in the contemporary Russian Federation. This article provides an analysis of the actions that Russia is planning and the actions that the country is taking to achieve Sustainable Development Goals (SDGs) 16 and 17 by 20 30. Aim and tasks. The study aims to identify the progress the Russia has made in achieving these two SDGs. To achieve the study’s aim, it is necessary to identify the crucial Sustainable Development Goals targets in the Russian context and analyse the approaches and measures taken to achieve these targets. Methods. The research is based on a case study (Russia), using a systematic analysis of a wide range of relevant academic and empirical sources published between 2020 and 2024. Results. The analysed sources suggest that Sustainable Development Goals targets 16.7 — “Ensure responsible decision-making by representative bodies at all levels with the participation of all sectors of society” and 17.16 — “Strengthen global partnerships” are crucial in the Russian context. The Russian Federation supports inclusiveness in political decision-making and strengthening multilateral partnerships to attain the SDGs. The respective approaches to the realisation of these two goals are modern and diversified. It is therefore challenging to evaluate progress towards their attainment using current indicators. Through novel, alternative pathways to the SDGs, a new statistical system needs to be developed so that progress can be tracked and measured. This article contributes to addressing research gaps in analysing Russia’s efforts to achieve Sustainable Development Goals targets 16.7 and 17.16. If these gaps can be eliminated, or at least minimised, it may be possible to assess Russia’s progress towards Sustainable Development Goals 16 and 17 more clearly. Conclusions. The author concludes that in order to fulfil Sustainable Development Goals targets 16.7 and 17.16, Russia is focusing its attention and efforts on creating conditions for an inclusive society and for the economic and social development of other countries.